Designing SPECA (Speaking Application) Based on an Android for Senior High School - Luluk choirun Nisak Nur; Soni Awaludin; Yuyun Bahtiar; Akhmad Kanzul Fikri (SCHOOLAR: Social and Literature Study in Education, 2023)
The purpose of this research is to design SPECA (Speaking Application) based on an android for speaking lessons for 11th-grade students of MA Hasanudin Klampisan Jombang. The researcher focused on speaking skill material for the first semester. This research used Research and Development method (R&D) that the researcher adapted from ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Based on the data on the development phase, the researcher got 62,22% on media validation which was categorized as a â€œworthy categoryâ€ classification. While the result of material validation was 62% also categorized as a â€œworthy categoryâ€ classification. After the product has been validated, the researcher tried out the product to know the response of the students toward the product. In this implementation phase, the researcher got 83% which could be categorized as an â€œinteresting categoryâ€. From the data that this research showed, it can be said that this application was feasible and can be applied to Senior High School Level.